Pengaruh Pelatihan dan Motivasi Kerja terhadap Kinerja Pegawai pada Dinas Kebudayaan dan Pariwisata Provinsi Sumatera Selatan - Sapna Sapna; Hamid Halin; Meilin Veronica (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this research is to analyze the relationship between training and job motivation at the Department of Culture and Tourism of South Sumatra Province. Saturated sampling was employed, in which all members of the population were used as samples, and a Google form questionnaire was used to gather data, which was then delivered to Civil Servants (PNS) using the WhatsApp social media platform. Multiple linear regression analysis was employed as the analytical technique for this quantitatively descriptive investigation. This study's t test and f test findings suggest that training and job motivation both positively and significantly affect employee performance in this context. This demonstrates that the theory put forth is correct. This study's findings show that training (X1) and work motivation (X2) have a synergistic, beneficial influence on productivity (Y). There is a favorable and substantial relationship between employee performance (Y) and both training (X1) and job motivation (X2) (Y). Training employees on a regular basis helps them do their jobs better, and it also gives them something to look forward to, which boosts morale. Positive workplace attitudes are critical to realizing the agency's vision and fulfilling its mission.